Intense Cooling of the Upper Ocean with the Merging of Tropical Cyclones: A Case Study in the Southeastern Indian Ocean - Oliver Wurl; Jens Meyerjürgens (Tellus: Series A, Dynamic Meteorology and Oceanography)
The thermodynamic responses of the upper ocean to interacting tropical cyclones (TCs) were investigated using in-situ observations, remote sensing products and numerical models. The interactions between TC Seroja and TC Odette in the southeastern Indian Ocean occurred between 6 April and 9 April 2021 (centered at 20°S, 110°E ± 5° each direction), and included a stalling of the smaller TC Odette by the passing of TC Seroja and subsequent complete merging. Multiple interactions with complete merging are very rare but represent one of the most extreme forms of air-sea interaction. Despite an insufficient ocean heat content, the merging led to an intensification of TC Seroja and to an extent of cooling (~3.0°C within 72 hours) by upwelling of deep water that was previously known in the literature only from stronger TCs. The stalling of the weak TC Odette (6 April, (15°S, 105°E) led to an unexpectedly intensive cooling by 2.5°C. Merging occurred on 9 April (20.5°S, 108.5°E), and with this interaction a sudden reversal from a downward to an upward velocity of up to 30 m d–1 was observed with subsequent transitions from maxima in downward and upward velocities (–10 to 10 m d–1). As a consequence, strong upwelling processes in the upper 200 m occurred, which were confirmed by in-situ data from ARGO floats. The frequency of concurrent formation and binary interaction between TCs could increase in the future with global warming and, with it, the extreme thermodynamic responses of the upper ocean.